The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1111/j.1525-1594.1990.tb01601.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and Endotoxin Contamination in Water and Dialysate in the Central United States

Abstract: The purified water supplies and randomly selected dialysates of 51 chronic and acute dialysis centers in the central United States were surveyed to assess the relative risks to dialysis patients from microbial and endotoxin contamination. A culture medium more sensitive than those generally employed in routine quality assurance assays was used for recovery of bacteria from water. With this medium, 35.3% of the water samples and 19% of the dialysate samples were out of compliance with the Association for the Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(12 citation statements)
references
References 15 publications
3
9
0
Order By: Relevance
“…Studies in Germany (Bambauer et al, 1994), Greece (Arvanitidou et al, 1998), the USA (Klein et al, 1990), and Canada (laurence and lapierre, 1995) revealed that even these moderate standards are not met, which is even more critical considering that a patient with chronic renal failure receives up to 400 l of dialysis fluid a week. Next to Gram-negative bacteria, cocci (micrococci, staphylococci, and streptococci) were found in the dialysate of 83, 70, and 10% of the centers, respectively, indicating the importance of Gram-positive contaminations.…”
Section: Dialysismentioning
confidence: 99%
See 1 more Smart Citation
“…Studies in Germany (Bambauer et al, 1994), Greece (Arvanitidou et al, 1998), the USA (Klein et al, 1990), and Canada (laurence and lapierre, 1995) revealed that even these moderate standards are not met, which is even more critical considering that a patient with chronic renal failure receives up to 400 l of dialysis fluid a week. Next to Gram-negative bacteria, cocci (micrococci, staphylococci, and streptococci) were found in the dialysate of 83, 70, and 10% of the centers, respectively, indicating the importance of Gram-positive contaminations.…”
Section: Dialysismentioning
confidence: 99%
“…Since then, contaminations have been found in the pure water (Klein et al, 1990;Pegues et al, 1992;Kulander et al, 1993;Bambauer et al, 1994), the machines, especially to areas with low circulation or dead spaces, which serve as a reservoir for bacteria (Phillips et al, 1994), filter materials (Schouten et al, 2000), and bicarbonate concentrates (Pegues et al, 1992).…”
Section: Dialysismentioning
confidence: 99%
“…Endotoxin testing reveals nothing about the levels of other microbiological contaminants, including yeasts, fungi, peptidoglycans, and fragments of bacterial DNA, all of which have been identified in water used for hemodialysis. [25][26][27]…”
Section: Where Do We Go From Here?mentioning
confidence: 99%
“…All of these arguments are predicated on the assumption that endotoxin levels are an adequate measure of water quality. Endotoxin testing reveals nothing about the levels of other microbiological contaminants, including yeasts, fungi, peptidoglycans, and fragments of bacterial DNA, all of which have been identified in water used for hemodialysis 25–27 …”
Section: Introductionmentioning
confidence: 99%
“…Surveys of dialysis fluid quality from the late 1980s show that many dialysis facilities did not comply with applicable standards for microbiological quality [4,5] . Changes in compliance since that time can be difficult to assess because of differences in how standards are implemented.…”
Section: Implementation Of Quality Standardsmentioning
confidence: 99%